New building development at cultural heritage building “Masjid Besar Cipaganti” Bandung - Utami Utami; Dede Rizkhianda Harahap; M Rafii Putra Atthariq; Havi Medio Nur Fauzan; Nazhif M Nazhim (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2023)
As one of the cultural heritage buildings, especially in the city of Bandung, the Cipaganti Great Mosque which is located on Jl. Cipaganti No 85 has historical value as well as its beauty and architectural uniqueness. Prof. Kemal C.P Wolff Schoemaker designed this mosque and began construction on February 7, 1933, until it was completed on January 27, 1934. Over time, there have been many changes in the Cipaganti Great Mosque building when compared to the initial building. Building development is needed at this time to meet capacity demands, which will affect the existence of the existing mosque building as a cultural heritage building. Overcoming these problems, it is necessary to conduct further research to identify the application of cultural heritage building elements to the Cipaganti Great Mosque by adding new buildings that aim to provide educational value to the community in the hope that historical values in this building and other buildings will not be lost and will continue to be sustainable. until whenever. This study uses a descriptive analysis method by making direct observations at the location of the Cipaganti Great Mosque by observing the building characteristics, functions, and architectural elements related to the development of new buildings. Based on the identification results, it was found that the new building of the Cipaganti Great Mosque still refers to the old building in its development process, both in exterior and interior elements, with modifications to the use of new materials.